Mathematical Modelling on RLCG Transmission Lines - Jiang, Y.-L. (Nonlinear Analysis: Modelling and Control, 2005)
A new model on RLCG transmissions lines is presented in the paper. The model suits to be taken to directly simulating a circuit system in timedomain. Mathematically, a circuit system with distributed elements may be described by a special kind of nonlinear integral-differential-algebraic equations with multiple constant delays.
Keywords: RLCG transmission lines; modelling; nonlinear circuits; integraldifferential-algebraic equations with multiple delays; simulation in timedomain